The transportome of the endophyte Serendipita indica in free life and symbiosis with Arabidopsis and its expression in moderate salinity - Haro, Rosario; Lanza, Mónica; Aguilella, Marcos; Sanz-García, Eugenio; Benito, Begoña (Frontiers in Microbiology, 2023)
Serendipita indica is an endophytic root symbiont fungus that enhances the growth of various plants under different stress conditions, including salinity. Here, the functional characterization of two fungal Na+/H+ antiporters, SiNHA1 and SiNHX1 has been carried out to study their putative role in saline tolerance. Although their gene expression does not respond specifically to saline conditions, they could contribute, together with the previously characterized Na+ efflux systems SiENA1 and SiENA5, to relieve Na+ from the S. indica cytosol under this stressed condition. In parallel, an in-silico study has been carried out to define its complete transportome. To further investigate the repertoire of transporters expressed in free-living cells of S. indica and during plant infection under saline conditions, a comprehensive RNA-seq approach was taken. Interestingly, SiENA5 was the only gene significantly induced under free-living conditions in response to moderate salinity at all the tested time points, revealing that it is one of the main salt-responsive genes of S. indica. In addition, the symbiosis with Arabidopsis thaliana also induced SiENA5 gene expression, but significant changes were only detected after long periods of infection, indicating that the association with the plant somehow buffers and protects the fungus against the external stress. Moreover, the significant and strongest induction of the homologous gene SiENA1 occurred during symbiosis, regardless the exposure to salinity. The obtained results suggest a novel and relevant role of these two proteins during the establishment and maintenance of fungus-plant interaction.